Selection Of Organic Fertilizer Supplier Using Analytical Hierarchy Process (Ahp) Method In Pt. Jmn Kabupaten Bandung (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Suppliers are an important part of a company's business activities, because quality suppliers will provide quality raw materials as well. PT. JMN is a company engaged in the agro-tourism business in which it carries out the process of agricultural management. One of the needs of PT. JMN is how to determine the supplier of organic fertilizers in accordance with the standards applied by the company. To solve these problems, the solution is carried out using the Analytical Hierarchy Process (AHP) method. The determination of decision-making elements for the AHP method is carried out by means of a Focus Group Discussion (FGD) with the management team. The result is that there are 5 criteria expected by the company and 3 alternative suppliers. After processing the data, it was found that the highest criteria expected by the company was quality with an importance weight of 47.3% and the chosen alternative was supplier A with a weight of 41.6%.